Seroprevalence of Toxoplasmosis in a Sample of Patients with Renal Failure (Journal of the College of Basic Education, 2024)
Toxoplasmosis is a prevalent transmissible disease worldwide, shared between humans and animals, caused by the parasite Toxoplasma gondii, a obligate intracellular protozoan parasite under the kingdom of single-celled animals Protozoa. It invades all types of nucleated cells. Toxoplasmosis is one of the most common opportunistic infections, particularly affecting patients with immunosuppression, kidney failure, organ transplant recipients, and acquired immunodeficiency. The current study aimed to investigate the prevalence of toxoplasmosis among patients with kidney failure and those attending the kidney dialysis unit in Baghdad Medical City, including 114 blood samples collected from the beginning of February to the end of April 2021, ranging in age from 21 to 80 years, as well as 36 blood samples from healthy individuals forming the control group. Blood samples were centrifuged at 3000 rpm for 5 minutes, serum was collected, distributed into 1 ml eppendorf tubes (250 microliters per tube), stored at -20 degrees Celsius in the life sciences laboratory of the Department of Basic Education Sciences at the University of Mustansiriya until use. أعلى النموذجAll samples were tested using the latex test Latex Agglutination(LA) test to diagnose infection with the protozoan parasite Toxoplasma gondii. The results showed that 53 samples, or 47%, tested positive, while 61 samples, or 53%, tested negative. The results were based on statistical analysis using the chi-square test, which showed no significant differences at a probability level of 0.05 based on factors such as gender, age, residence, smoking, presence of cats in the household, as well as no association between Toxoplasma gondii infection in patients with renal failure and the presence of certain chronic diseases such as diabetes and hypertension.